Proceedings of Latin American &Amp; Caribbean Petroleum Engineering Conference 2007
DOI: 10.2523/106679-ms
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Upscaling Techniques for Reservoir Simulation

Abstract: Upscaling reservoir properties for reservoir simulation is one of the most important steps in the workflow for building reservoir models. Upscaling allows taking high-resolution geostatistical models (10 7 -10 8 grid blocks) to coarse scale models (10 4 -10 5 grid blocks), manageable for reservoir simulation, while retaining the geological realism and thus effectively representing fluid transport in the reservoir 1,2 . This work presents a study of the effectiveness of different available techniques for permea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…: pore volume of sample , cm 3 : bulk volume of sample , cm 3 ∅: effective porosity , fraction The permeability was measured for the all core plug samples using the conventional steady state method with injecting of nitrogen gas through the plug samples with known viscosity of the applied gas, Figure ( The gas permeability for all samples were run with five points of mean pore pressure including (150,175,200, 225,250) psi respectively. The results of gas apparent permeabilities of each sample were plotted with the inverse of applied pore pressure for each permeability measurement, as shown in Figure (5). A straight line is interconnected all points and intersects the y-axis (apparent) permeability where inverse of pore pressure equal to zero presents the mean pore pressure tends to infinity [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…: pore volume of sample , cm 3 : bulk volume of sample , cm 3 ∅: effective porosity , fraction The permeability was measured for the all core plug samples using the conventional steady state method with injecting of nitrogen gas through the plug samples with known viscosity of the applied gas, Figure ( The gas permeability for all samples were run with five points of mean pore pressure including (150,175,200, 225,250) psi respectively. The results of gas apparent permeabilities of each sample were plotted with the inverse of applied pore pressure for each permeability measurement, as shown in Figure (5). A straight line is interconnected all points and intersects the y-axis (apparent) permeability where inverse of pore pressure equal to zero presents the mean pore pressure tends to infinity [29].…”
Section: Methodsmentioning
confidence: 99%
“…Permeability is an essential parameter for the evaluation of reservoir potentiality and production rate estimation of a specific field. In addition, this parameter can be used in reservoir simulation of particular rock type [1,2,3,4,5]. The liquid permeability only measure for a specific rock interval and from a limited number of core samples.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a high permeability streak channel in a reservoir region often leads to early water breakthrough, computing effective absolute permeability together with original rock relative permeabilities cannot capture this behaviour, unless a multi-phase upscaling is performed. Salazar et al (2007) in their studies concluded that the two-phase upscaling generated better flow behaviour than the single-phase upscaling. They further stated that the most important aspect in upscaling is the upscaling ratio, which determines the accuracy of production predictability.…”
Section: Single-phase or Multi-phase Upscaling?mentioning
confidence: 99%